Native american feminism, sovereignty, and social change - Smith, Andrea (Feminist Studies, 2005)
Smith argues that any serious conceptualization of Native American women as feminist activists demands a rejection of the reductive dichotomy of feminist versus nonfeminist. For her, one must first understand the diversity of opinions about feminist activism that exists among Native women and how they have uniquely conceived both their role as activists and their theoretical frameworks. In addition, for many Native women the traditional assumption that a feminist's first aim is to combat sexism is inadequate for dealing with the equally important problem of Native American sovereignty.
Keywords: 2000 à aujourd'hui; 2000-2009; OFDIG; approches et analyses; féminisme autochtone; intersectionnalité; périodes historiques; ressource en ligne; thématiques; violences; violences coloniales; violences contre les femmes*; violences sexuelles